2021
DOI: 10.1186/s13148-021-01071-z
|View full text |Cite
|
Sign up to set email alerts
|

DNA hypermethylation contributes to colorectal cancer metastasis by regulating the binding of CEBPB and TFCP2 to the CPEB1 promoter

Abstract: Background Aberrant DNA methylation has been firmly established as a factor contributing to the pathogenesis of colorectal cancer (CRC) via its capacity to silence tumour suppressor genes. However, the methylation status of multiple tumour suppressor genes and their roles in promoting CRC metastasis are not well characterised. Methods We explored the methylation and expression profiles of CPEB1 (the gene encoding cytoplasmic polyadenylation element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…For example, CEBPB À/À mice are completely resistant to papilloma induced by chemical carcinogens [44], which was in accord with our report that silencing of CEBPB can increase ASS1 expression and alleviate the malignant biological behaviors and tumor progression. Indeed, CEBPB was identified to directly bind to the promoter of cytoplasmic polyadenylation element-binding protein 1, and thus, could inhibit transcription [45]. Veremeyko et al [46] showed that CEBPB is highly expressed in M1 macrophages, and it appears to inhibit Egr2, leading to loss of plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CEBPB À/À mice are completely resistant to papilloma induced by chemical carcinogens [44], which was in accord with our report that silencing of CEBPB can increase ASS1 expression and alleviate the malignant biological behaviors and tumor progression. Indeed, CEBPB was identified to directly bind to the promoter of cytoplasmic polyadenylation element-binding protein 1, and thus, could inhibit transcription [45]. Veremeyko et al [46] showed that CEBPB is highly expressed in M1 macrophages, and it appears to inhibit Egr2, leading to loss of plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Many pathways are associated with the pathogenesis of CD. [124], TLR8 [125], HTRA3 [126], CEBPB (CCAAT enhancer binding protein beta) [127], CD55 [128], CXCR2 [129], CCL28 [130], CBR3 [131], CCL3 [132], FCGR2A [48], ACSL1 [133], CCL2 [134], SOD2 [135], CD14 [136], IGFBP2 [137], CD274 [138], DERL3 [139], SERPINE1 [140], IDO1 [141], PDK1 [142] [156], TYMP (thymidine phosphorylase) [144], S100P [157], PDPN (podoplanin) [158], ADAMTS1 [159], ATF3 [160], TIMP1 [161], UCN2 [162], SELE (selectin E) [163], ICAM1 [164], FOSL1 [165], AREG (amphiregulin) [166], PIM2 [167], SLC7A5 [168], CH25H [169], COL5A2 [170], SNAI1 [171], MXRA5 [172], EGR1 [173], TNFRSF17 [174], MDFI (MyoD family inhibitor) [175], SRGN (serglycin) [176], CEACAM6 [177], CCL11 [178], IFNG (interferon gamma) [179], TREM2 [180], INHBA (inhibin subunit beta A) [181], APOE (apolipoprotein E) [182], FGR (FGR proto-oncogene, Src family tyrosine kinase) GBP5 [465], HGF (hepatocyte growth factor) [466], CXCL9 [467], SLC11A1 [468], IL1RN [469], STAT1 [470], CYP27B1 [471], MMP1 [472], SOCS3 [473], TLR8 [474], CD55 [475], CCL28 [476], FCGR2A [477], CCL2 [478],...…”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathway include immune system [69], neutrophil degranulation [70], cytokine signaling in immune system [71], extracellular matrix organization [72], post-translational protein phosphorylation [73], biological oxidations [74], metabolism [75] and metabolism of lipids [76] were responsible for progression of CD. CXCL5 [77], CXCL3 [78], PROK2 [79], CXCR1 [80], PYCR1 [81], OSM (oncostatin M) [82], IL15RA [83], LRG1 [84], LCN2 [85], BATF2 [86], CXCL1 [87], S100A9 [88], IFITM1 [89], MYOF (myoferlin) [90], XBP1 [91], MMP3 [92], TAP1 [93], FPR2 [94], CXCL6 [95], C2CD4A [96], IFITM3 [97], IL1B [98], SLC6A14 [99], FPR1 [100], NOS2 [101], CHI3L1 [102], TGM2 [103], MUC4 [104], TREM1 [105], WNT5A [106], HGF (hepatocyte growth factor) [107], CXCL9 [108], GBP1 [109], S100A11 [110], ADM (adrenomedullin) [111], CXCL11 [112], CXCL10 [113], LILRB2 [114], GDF15 [115], IL1RN [116] STAT1 [117], SLAMF7 [105], CYP27B1 [118], NETO2 [119], TFPI2 [120], ZC3H12A [121], MMP1 [122], CSF3 [123], SOCS3 [124], TLR8 [125], HTRA3 [126], CEBPB (CCAAT enhancer binding protein beta) [127], CD55 [128], CXCR2 [129], CCL28 [130], CBR3 [131], CCL3 [132], FCGR2A [48], ACSL1 [133], CCL2 [134], SOD2 [135], CD14 [136], IGFBP2 [137], CD274 [138], DERL3 [139], SERPINE1 [140], IDO1 [141], PDK...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been demonstrated that CEBPB is the master regulator of macrophage differentiation, which could define the macrophage identity by marking the macrophage-specific chromatin regulatory elements for the following TF binding ( 21 ). The regulatory roles of CEBPB in the onset of cancer and the progression of its transcriptional regulatory function in malignant cells have also been uncovered ( 22 , 23 ). A few studies have also reported potential associations between CEBPB and metastasis ( 24 ) or treatment response in melanoma ( 25 ).…”
Section: Introductionmentioning
confidence: 99%